2020
DOI: 10.21203/rs.2.21087/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

tRNA queuosine modification enzyme modulates the growth and microbiome recruitment to breast tumors

Abstract: Background: Transfer RNA (tRNA) queuosine (Q)-modifications occur specifically in 4 cellular tRNAs at the wobble anticodon position. tRNA Q-modification in human cells depends on the gut microbiome because the microbiome product queuine is required for its installation by the enzyme queuine tRNA ribosyltransferase catalytic subunit 1 (QTRT1) encoded in the human genome. Although tRNA Q-modification has been studied a long time regarding its properties in decoding and tRNA fragment generation, how QTRT1 affects… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“… 35 In our recent study, we found Butyrivibrio fibrisolvens -related clones, which belong to the Firmicutes phylum, in breast tumors with a xenograft mouse model. 36 …”
Section: Breast Microbiome and Breast Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“… 35 In our recent study, we found Butyrivibrio fibrisolvens -related clones, which belong to the Firmicutes phylum, in breast tumors with a xenograft mouse model. 36 …”
Section: Breast Microbiome and Breast Diseasesmentioning
confidence: 99%
“…For example, the systemic counter-interactions between microbes and immune items of IL-6 and neutrophils have been indicated in breast cancer. 36 , 72 It is known that both neutrophils and lymphocytes are modulated by the microbiota and inflammation. The neutrophil-associated immune responses to the GI microbiome significantly impact carcinogenesis progress in non-intestinal tissues, such as mammary glands.…”
Section: Gut Microbiome and Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…However, they are important metabolites that speci cally modify certain human tRNAs to promote protein folding 9,45,46 . The speci c role that these metabolites play in humans remains under investigation, though there is at least some evidence that they may also have anti-cancer activity in addition to their regulatory roles in commensal bacteria 47,48 . Here, we demonstrate that PreQ1 also has speci c interactions with important regulatory human RNAs, including TERC, HIST1H3F, and HIST2H2BF, all of which have been shown previously to form stable RNA structures.…”
Section: Resultsmentioning
confidence: 99%